The clinical features, treatment and prognosis of neutropenic fever and Coronavirus disease 2019 results of the multicentre teos study - Elik, Dilsah Baskol; Kaya, Safak; Alkan, Sevil; Demirdal, Tuna; Sener, Alper; Kaya, Selcuk; Sipahi, Oguz Resat (Nature Portfolio, 2024)
This multicentre (22 centres in Turkey) retrospective cohort study aimed to assess the clinical outcomes of patients with neutropenic fever and SARS-CoV-2 positivity. Study period was 15 March 2020-15 August 2021. A total of 170 cases (58 female, aged 59 +/- 15.5 years) that fulfilled the inclusion criteria were included in the study. One-month mortality rate (OMM) was 44.8%. The logistic regression analysis showed the following significant variables for the mentioned dependent variables: (i) achieving PCR negativity: receiving a maximum of 5 days of favipiravir (p = 0.005, OR 5.166, 95% CI 1.639-16.280); (ii) need for ICU: receiving glycopeptide therapy at any time during the COVID-19/FEN episode (p = 0.001, OR 6.566, 95% CI 2.137-20.172), the need for mechanical ventilation (p < 0.001, OR 62.042, 95% CI 9.528-404.011); (iii) need for mechanical ventilation: failure to recover from neutropenia (p < 0.001, OR 17.869, 95% CI 3.592-88.907), receiving tocilizumab therapy (p = 0.028, OR 32.227, 95% CI 1.469-707.053), septic shock (p = 0.001, OR 15.4 96% CI 3.164-75.897), and the need for ICU (p < 0.001, OR 91.818, 95% CI 15.360-548.873), (iv) OMM: [mechanical ventilation (p = 0.001, OR 19.041, 95% CI 3.229-112.286) and septic shock (p = 0.010, OR 5.589,95% CI 1.509-20.700)]. Although it includes a relatively limited number of patients, our findings suggest that COVID-19 and FEN are associated with significant mortality and morbidity.
Keywords: Covid-19; Cancer; Severity